Synthesis, characterization and biological activity of the Cu (II)-1,3-PDTA [(Cu (II) (PDTA)] complex for the control of Erwinia chrysanthemi (soft rot) in the parsley manioc (Arracacia xanthorrhiza Bancroft) - Teixeira, Cristiane Freitas de Almeida (2025)
Synthesis, characterization and biological activity of the Cu(II)-1,3-PDTA complex was performed by two synthetic routes: sodium and carbonate pathways. The Cu (II)-1,3-PDTA complex can be easily produced by the 1,3-PDTA binder, commercially available as Trilon F (BASF) which is available as sodium or acid salt for the coordination of Cu (II). The biological activity of the Cu (II)-1,3-PDTA [Cu (II)-PDTA] complex was performed to analyze the activity against the bacterium Erwinia chrysanthemi Bancroft. The bacterium is the causative agent of soft rot in the parsley maniac (Arracacia xanthorrhiza Bancroft). The bacterium was isolated from parsley manioc infected with soft rot. The metal complex sensitivity tests were performed by diffusion antibiogram. The mean values of the halos and standard deviations of the zones of inhibition were obtained for the [Cu (II) (PDTA)] and Streptomycin complexes. The concentrations of the complexes evaluated were 10-3, 10-2 and 10-1 M (equivalent to 36.3 g L-1 (3.63%), 3.63 g L-1 (0.363%) and 0.363 g L-1 (0.0363%), respectively). The halos were 25.0 ± 1.2 mm for control. For [Cu (II) (PDTA)] complexes, the obtained values were 9.5 ± 0.6, 15.0 ± 0.8 and 24.0 ± 0.8 via sodium and 12.0 ± 1.6, 25.0 ± 0.8 and 31.0 ± 1.9 via carbonate, for 10-3, 10-2 and 10-1 M, respectively. The results showed that the bactericidal activity of the Cu (II)-1,3-PDTA complex obtained by the two synthetic routes are adequate for the control of Erwinia chrysanthemi Bancroft.